Hepatitis B and Delta: clinical aspects of patients in the Brazilian Western Amazonia - Marcelo Siqueira de Oliveira; Romeu Paulo Martins Silva; Suiane da Costa Negreiros do Valle; Rodrigo Medeiros de Souza; Elisabeth Níglio de Figueiredo; Mônica Taminato; Dayana Souza Fram
ABSTRACT Objective: to analyze clinical, serological, biochemical and hematological aspects in patients infected with the hepatitis B (HBV) and Delta (HDV) viruses. Method: cross-sectional, descriptive and retrospective study, performed with patients chronically infected with HBV and superinfected with HDV. Results: among the 112 patients selected, 74% were monoinfected with HBV (Group HBV) and 26% were superinfected with HDV (Group HBV+HDV). There was no difference in gender distribution. The average age was 36 years with standard deviation of ±12 years. The symptoms and signs presented a higher proportion in Group HBV+HDV (p=0.001). In both groups, most patients had non-reactive AgHBe. The records of biochemical and hematologic changes showed highest proportion in Group VHB+VHD Group (p<0.05). Conclusion: the study found that patients were in clinical stages of the disease different from those in the initial examination for monitoring their chronic condition. The clinical profile suggests greater severity of liver disease among the patients superinfected with HDV.